Integrating a formal method into a software engineering process with UML and Java - Möller, Michael; Olderog, Ernst-Rüdiger; Rasch, Holger; Wehrheim, Heike (Formal Asp. Comput.)

Slicing Abstractions - Brückner, Ingo; Dräger, Klaus; Finkbeiner, Bernd; Wehrheim, Heike (Fundam. Inform.)

From UML Activities to TAAL - Towards Behaviour-Preserving Model Transformations - Engels, Gregor; Kleppe, Anneke; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike (Model Driven Architecture - Foundations and Applications, 4th European Conference, ECMDA-FA 2008, Berlin, Germany, June 9-13, 2008. Proceedings)

Mechanizing a Correctness Proof for a Lock-Free Concurrent Stack - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems, 10th IFIP WG 6.1 International Conference, FMOODS 2008, Oslo, Norway, June 4-6, 2008, Proceedings)

Decomposition for Compositional Verification - Metzler, Björn; Wehrheim, Heike; Wonisch, Daniel (Formal Methods and Software Engineering, 10th International Conference on Formal Engineering Methods, ICFEM 2008, Kitakyushu-City, Japan, October 27-31, 2008. Proceedings)

Bounded Model Checking for Partial Kripke Structures - Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2008, 5th International Colloquium, Istanbul, Turkey, September 1-3, 2008. Proceedings)

Reference Models and Modeling Languages for Product-Service Systems --- Status-Quo and Perspectives for Further Research - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Proceedings of the 41th Hawai'i International Conference on System Sciences)

Modeling, Customer-Specific Configuration and Calculation of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Americas Conference on Information Systems)

Konfigurative Prozessmodellierung der hybriden Leistungserstellung in Unternehmensnetzwerken des Maschinen- und Anlagenbaus - Beverungen, Daniel; Kaiser, Uwe; Knackstedt, Ralf; Krings, Robin; Stein, Armin (Proceedings of the Multikonferenz Wirtschaftsinformatik (MKWI 2008))

Improving the Quality of Article Master Data --- Specification of an Integrated Master Data Platform for Promotions in Retail - Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian; Becker, Jörg (Proceedings of the 16th European Conference on Information Systems)

Entwicklung Serviceorientierter Architekturen zur Integration von Produktion und Dienstleistung --- Eine Konzeptionsmethode und ihre Anwendung am Beispiel des Recyclings elektronischer Geräte - Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Wirtschaftsinformatik)

Unternehmensbewertung für substanzsteuerliche Zwecke - eine empirische Analyse des Stuttgarter Verfahrens und alternativer Ansätze - Müller, Jens
Über 50 Jahre wurde das Stuttgarter Verfahren verwendet, um den Wert nicht börsennotierter Unternehmen für die Erbschaft-, Schenkung- und Vermögensteuer zu bestimmen. Durch das Urteil des Bundesverfassungsgerichts vom 07.11.2006 ist der Gesetzgeber verpflichtet, die Erbschaftsteuer zu reformieren und eine marktnahe Bewertung von Unternehmensvermögen sicherzustellen. Auf der Basis einer umfangreichen empirischen Analyse geht Jens Müller den Fragen nach, wie stark eine Bewertung durch das Stuttgarter Verfahren von Marktwerten abweicht und in welchen Fällen eine akzeptable Approximation des Marktwertes erreicht wird. In der Praxis wird das Multiplikatorverfahren häufig zur Bewertung nicht börsennotierter Unternehmen verwendet. Der Autor untersucht, in welcher Form dieses Verfahren auch für steuerliche Zwecke geeignet ist und zeigt auf, mit welchen Schätzfehlern zu rechnen ist.
Keywords: Steuer-; Rechnungs- und Prüfungswesen

Intuition and professional competence: Intuitive versus rational forecasting of the stock market - Harteis, Christian; Gruber, Hans (Vocations and Learning)

Emerging perspectives of workplace learning

The culture of learning from mistakes: How employees handle mistakes in everyday work - Harteis, Christian; Bauer, Johannes; Gruber, Hans (International Journal of Educational Research)

The workplace as learning environment: Introduction - Harteis, Christian; Billett, Stephen (International Journal of Educational Research)

How important is intuition for teaching expertise in the field of adult education? - Harteis, Christian; Gruber, Hans (Studies in the Education of Adults)

How Intuition Contributes to High Performance: An Educational Perspective. - Harteis, Christian; Koch, Tina; Morgenthaler, Barbara (US-China Education Review)

Lernende Region Cham Programmvertiefung II Kommunale Kooperation Waldmünchen - Gruber, Hans; Harteis, Christian; Paetz, Nadja-Verena; Keil, Stefanie

Lernen und Lehren im Erwachsenenalter - Gruber, Hans; Harteis, Christian (Lehrbuch Pädagogische Psychologie)